2013
DOI: 10.1007/s00381-013-2201-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of tumor spheres and mesenchymal stem-like cells from a single primitive neuroectodermal tumor specimen

Abstract: We showed that both tumor spheres and MSLCs can be isolated from the same PNET specimen. PNET-MSLCs occupied a niche in the vicinity of the vasculature and could be a source of stroma for PNETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Thus, optimal conditions, including rapid transfer of specimens following surgical resection, removal of red blood cells and necrotic material and an appropriate environment for growth are required for the isolation of TSs from fresh surgical specimens [5,7,9,11,12,18,19,23,35]. Our laboratory has an ongoing effort to develop optimal conditions for the isolation of TS [2,3,10,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, optimal conditions, including rapid transfer of specimens following surgical resection, removal of red blood cells and necrotic material and an appropriate environment for growth are required for the isolation of TSs from fresh surgical specimens [5,7,9,11,12,18,19,23,35]. Our laboratory has an ongoing effort to develop optimal conditions for the isolation of TS [2,3,10,17].…”
Section: Discussionmentioning
confidence: 99%
“…When cultured under appropriate conditions in vitro, this population of tumor cells gives rise to gliomaspheres, referred to more generically as tumorspheres (TSs). TSs have been isolated from various malignant tumors, including breast [4], prostate [5], bone [6], colon [7], kidney [8] and lung [9], as well as brain [3,[10][11][12][13][14]. It was previously reported that the rate of isolation of TSs increase as the World Health Organization (WHO) grades of glioma rise [3].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem-like cells (MSLCs) have been isolated from normal brain [ 6 , 7 ] and Lang et al [ 8 ] presented the isolation of mesenchymal stem cells (MSCs) from glioma for the first time. In addition, tumor MSLCs (tMSLCs) have been isolated from several human brain tumors [ 2 , 9 11 ], suggesting that these cells play a role in creating a microenvironment conducive to brain tumor initiation and progression [ 2 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathologists diagnosed each surgical specimen according to the WHO classification criteria (19). TSs were isolated from the rPB specimen using a modification of previous methods for TS isolation from human brain cancers (11,13,15,20,21). Briefly, the cell isolation procedure was performed within 60 min of PB removal using a mechanical dissociation method.…”
Section: Methodsmentioning
confidence: 99%
“…Neuro-glial differentiation. The multipotency of rPB TSs was tested by examining neural lineage expression by immunocytochemical staining, as previously described (11,20,26). Briefly, after being seeded onto chamber slides (Lab-Tek II; Nalge Nunc International, Rochester, NY, USA), cells were grown in neural differentiation media containing 10% fetal bovine serum (FBS; Lonza) and 1X B27 supplement (Invitrogen) for up to 14 days.…”
Section: Reverse-transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%